2005
DOI: 10.1111/j.1550-7408.2005.3309rr.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐type Proton ATPases are Involved in Intracellular Calcium and Proton Uptake in the Plant Parasite Phytomonas francai

Abstract: The use of digitonin to permeabilize the plasma membrane of promastigotes of Phytomonas francai allowed the identification of two non-mitochondrial Ca(2+) compartments; one sensitive to ionomycin and vanadate (neutral or alkaline), possibly the endoplasmic reticulum, and another sensitive to the combination of nigericin plus ionomycin (acidic), possibly the acidocalcisomes. A P-type (phospho-intermediate form) Ca(2+)-ATPase activity was found to be responsible for intracellular Ca(2+) transport in these cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…ϩ -ATPase Activity in Permeabilized Procyclic Forms-Previous studies using permeabilized T. cruzi (37) and Phytomonas francai (38) cells demonstrated the presence of intracellular vanadate-sensitive (P-type) H ϩ -ATPases activities. In the case of T. cruzi, a vanadate-sensitive H ϩ -ATPase is localized in its endocytic compartment (15).…”
mentioning
confidence: 99%
“…ϩ -ATPase Activity in Permeabilized Procyclic Forms-Previous studies using permeabilized T. cruzi (37) and Phytomonas francai (38) cells demonstrated the presence of intracellular vanadate-sensitive (P-type) H ϩ -ATPases activities. In the case of T. cruzi, a vanadate-sensitive H ϩ -ATPase is localized in its endocytic compartment (15).…”
mentioning
confidence: 99%
“…Thapsigargin and IP 3 were not able to affect the vanadate-sensitive Ca 2+ transport. Such an effect of digitonin has been attributed, in some cases, to the cell growth medium composition (Zhang et al 1998 ;Miranda et al 2005). No evidence of a third Ca 2+ compartment with the characteristics of the acidocalcisomes described by Vercesi et al (1994) was observed in those experiments.…”
Section: Introductionmentioning
confidence: 87%
“…For this reason, they have been considered to correspond to volutin or metachromatic granules described previously in some bacteria and protists (Kornberg 1995; Meyer 1904). Acidocalcisomes have been characterized by their acidic nature, high electron density, and high concentration of elements, such as Na, Mg, P, K, Ca, Fe, and Zn, which can be detected either by fluorimetric assays using appropriate fluorescent probes (Miranda et al 2005; Vercesi et al 1994) or by analytical electron microscopy (LeFurgey et al 2005; Miranda et al 2000, 2004a, b, c, 2008; Scott et al 1997; Vickerman and Tetley 1977). Cation uptake and release and water transport across these organelles are powered by a number of ion pumps (i.e.…”
mentioning
confidence: 99%